ICU Bed Utilization During the Coronavirus Disease 2019 Pandemic in a Multistate Analysis—March to June 2020. (12th March 2021) - Douin, David J.; Ward, Michael J.; Lindsell, Christopher J.; Howell, Michelle P.; Hough, Catherine L.; Exline, Matthew C.; Gong, Michelle N.; Aboodi, Michael S.; Tenforde, Mark W.; Feldstein, Leora R.; Stubblefield, William B.; Steingrub, Jay S.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: Given finite ICU bed capacity, knowledge of ICU bed utilization during the coronavirus disease 2019 pandemic is critical to ensure future strategies for resource allocation and utilization. We sought to examine ICU census trends in relation to ICU bed capacity during the rapid increase in severe coronavirus disease 2019 cases early during the pandemic. Design: Observational cohort study. Setting: Thirteen geographically dispersed academic medical centers in the United States. Patients/Subjects: We obtained daily ICU censuses from March 26 to June 30, 2020, as well as prepandemic ICU bed capacities. The primary outcome was daily census of ICU patients stratified by coronavirus disease 2019 and mechanical ventilation status in relation to ICU capacity. Interventions: None. Measurements and Main Results: Prepandemic overall ICU capacity ranged from 62 to 225 beds (median 109). During the study period, the median daily coronavirus disease 2019 ICU census per hospital ranged from 1 to 84 patients, and the daily ICU census exceeded overall ICU capacity for at least 1 day at five institutions. The number of critically ill patients exceeded ICU capacity for a median (interquartile range) of 17 (12–50) of 97 days at these five sites. All 13 institutions experienced decreases in their noncoronavirus disease ICU population, whereas local coronavirus disease 2019 cases increased. Coronavirus disease 2019 patients reached their greatest proportion of ICU capacity on April 12, 2020, when they accounted for 44% of ICU patients across all participating hospitals. Maximum ICU census ranged from 52% to 289% of overall ICU capacity, with three sites less than 80%, four sites 80–100%, five sites 100–128%, and one site 289%. Conclusions: From March to June 2020, the coronavirus disease 2019 pandemic led to ICU censuses greater than ICU bed capacity at fives of 13 institutions evaluated. These findings demonstrate the short-term adaptability of U.S. healthcare institutions in redirecting limited resources to accommodate a public health emergency.